2012
DOI: 10.1063/1.4739315
|View full text |Cite
|
Sign up to set email alerts
|

Merged-beams for slow molecular collision experiments

Abstract: Molecular collisions can be studied at very low relative kinetic energies, in the milliKelvin range, by merging codirectional beams with much higher translational energies, extending even to the kiloKelvin range, provided that the beam speeds can be closely matched. This technique provides far more intensity and wider chemical scope than methods that require slowing both collision partners. Previously, at far higher energies, merged beams have been widely used with ions and/or neutrals formed by charge transfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Two recent developments, the merged beam technique and low-angle crossed beam scattering, have finally enabled scientists to venture into this regime and to observe resonances in other reactions as well. [12][13][14][15] Most studies of scattering resonances to date targeted collisions involving atoms or diatomic molecules. [14][15][16][17][18] We are aware of only two other studies where resonances were observed in the elastic scattering of polyatomic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent developments, the merged beam technique and low-angle crossed beam scattering, have finally enabled scientists to venture into this regime and to observe resonances in other reactions as well. [12][13][14][15] Most studies of scattering resonances to date targeted collisions involving atoms or diatomic molecules. [14][15][16][17][18] We are aware of only two other studies where resonances were observed in the elastic scattering of polyatomic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The key idea behind the merged beams method is that by studying collisions in two molecular beams that are merged into a single beam, the collision angle is zero and the relative velocity of the reactants in the moving frame of reference becomes simply the difference between the two beam speeds. 23 In contrast to a crossed beams experiment this can become zero even at high beam velocities, thus rendering the slowing of the molecules unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reach collision energies corresponding to temperatures below 1 K, two supersonic beams travelling at the same speed need to be crossed at an angle close to 0 • . 62 This can be achieved by merging two reactant beams into a single beam-for example, by bending one beam onto the other such that they converge to the same axis. In systems where one of the species has no magnetic moment, a curved magnetic guide can be employed to direct LFS paramagnetic species onto the axis of a second (nonparamagnetic) beam of particles (Figure 2).…”
Section: Merged Beamsmentioning
confidence: 99%